The Relationship between Perception of Father Parenting Style and Religiosity of the Adolescent Pastor’s Children - Jonathan, Margareth; Gunawan, William (Veritas : Jurnal Teologi dan Pelayanan, 2021)
Ideally, a pastor’s child is a role model in religious life. However, a pastor’s child has some religious problems rooted in parental influence. This research aimed to determine whether each parenting style correlated with the religiosity of a pastor’s child. This research hypothesizes that there was a significant correlation between the perceptions of authoritarian parenting, authoritative parenting, permissive parenting, and uninvolved parenting with the religiosity of adolescent pastors’ children. The sampling technique used was purposive sampling. As many as 172 Indonesian pastors’ children aged 13 to 17 years old participated in this study. The measuring instrument used were the Parenting Style measure and the Centrality of Religiosity (CRS). The research method is quantitative correlational research. The research results indicate no correlation between each type of parenting style and religiosity. As much as 76.7% of the pastors’ children were at the religious level, followed by 14% who were not religious and 9.3% were very religious. The research implied that the influence of religiosity in the life of the pastors’ children is not due to their fathers’ parenting styles. This study provides several practical implications. The pastor’s family (especially the father) can still apply authoritative parenting because it has positively impacted a child’s development and personality. The church needs to build an authentic faith community to support the development of healthy spirituality and religiosity for adolescent pastors' children.